2014
DOI: 10.1002/2013jd019813
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of multiscale variations of decade-long cloud fractions from six different platforms over the Southern Great Plains in the United States

Abstract: This study compares 1997-2011 observationally based cloud fraction estimates from six different platforms (three ground-based estimates and three satellite-based estimates) over the Southern Great Plains, United States. The comparisons are performed at multiple temporal and spatial scales. The results show that 1997-2011 mean cloud fractions from the Active Remote Sensing of CLouds (ARSCL) and from the International Satellite Cloud Climatology Project (ISCCP) are significantly (at a 2% significance level, two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 82 publications
2
38
0
Order By: Relevance
“…2.3 and 2.4. Note that the interpretation of CF estimates and 1-D column CF estimate representativeness is often nontrivial (e.g., Wu et al, 2014). This study defines CF as the fraction of observations (heightresolved or over the entire column) within an hour for which the combined profiling sensors identify clouds overhead.…”
Section: Arm Mobile Facility Cloud Observationsmentioning
confidence: 99%
“…2.3 and 2.4. Note that the interpretation of CF estimates and 1-D column CF estimate representativeness is often nontrivial (e.g., Wu et al, 2014). This study defines CF as the fraction of observations (heightresolved or over the entire column) within an hour for which the combined profiling sensors identify clouds overhead.…”
Section: Arm Mobile Facility Cloud Observationsmentioning
confidence: 99%
“…All of these factors can cause differences between the cloud cover amounts at a specific location and time even if the cloud is correctly detected by the respective observing systems, as discussed by Wu et al (2014). Cloud cover at weather stations, on the other hand, is visually reported following the WMO synoptic code.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a substantial satellite-based cloud record has been collected for decades. Several studies have found large discrepancies in cloud cover reports when comparing sparse ground measurements to satellite data (McKenzie et al, 1998;Wu et al, 2014). Passive sensors can be associated with some uncertainties related to observation geometry challenges (Norris, 2000;Warren and Hahn, 2002).…”
Section: Introductionmentioning
confidence: 99%